Violence against women and girls with disabilities during and after the 2015 Nepal earthquake: thematic analysis of qualitative data - Sapana Basnet Bista, MPhil; Shaurabh Sharma, MA (Elsevier, 2019)
Background: Disasters affect people with disabilities disproportionately. Violence against women and girls, including sexual and psychological violence, has been reported to increase during and after natural disasters. Despite worldwide attention on the devastation caused by the 2015 earthquake in Nepal, the risk of violence against women and girls with disabilities and their experiences during the crisis and recovery phases remain under-researched. In this study, we aim to explore the experiences of violence against disabled women and girls immediately after the earthquake and during the post-earthquake recovery period. Methods: We undertook a thematic analysis of qualitative data collected through semi-structured interviews and focus group discussions with women and girls with disabilities from the districts worst affected by the 2015 Nepal earthquake: Kathmandu valley (n=16), Dhading (n=8), Sindhupalchok (n=8), and Gorkha (n=8). These qualitative data were a part of two larger studies; one that explored the experiences of people with disabilities during the 2015 Nepal earthquake and another that studied the effect of post-earthquake mental health and psychosocial support in women with disabilities. All participants for this part of the study were recruited through a snowball sampling technique. Findings: We analysed data from interviews with 40 participants conducted between May, 2015, and February, 2018. Five focus group discussions each with eight participants lasted between 1 h and 1·5 h. Semi-structured interviews lasted between 30 mins and 45 mins. By comparison with their pre-earthquake experiences, women and girls with disabilities reported increased psychological, physical, and sexual violence immediately after the earthquake mostly in and around temporary shelters. Physical and psychological violence were reported to be committed by partners, family members, relatives, and sometimes by people who lived in the same community; sexual violence against girls with disabilities were reported to be committed by close relatives, family members, or an opportunist stranger. Interpretation: Our findings highlight that being female with a disability, having limited rights and independence, and having limited access to financial resources lead to increased longer-term violence, even during the recovery and reconstruction phase of a natural disaster. We recommend that emergency responders undertake gender and disability sensitisation training to remove barriers and stigma against women and girls with disabilities. Government, national, and international humanitarian agencies should work together with local-level organisations to strengthen gender and disability-inclusive preventative, reporting, and justice mechanisms. Funding: None.